Method for upgrading and recycling polyvinyl chloride through mechanochemical catalysis
By using TiO2 catalyst to react with PVC and olefins or alcohol in the ball mill system, environmental pollution and waste of chlorine resources caused by alkaline additives in the prior art are solved, and efficient degradation of polyvinyl chloride and recycling of chlorine elements are achieved.
Patent Information
- Application Number
- CN202510654141.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-21
- Publication Date
- 2025-08-26
AI Technical Summary
In the existing mechanochemical dechlorination polyvinyl chloride method, the use of alkaline additives leads to environmental pollution and waste of chlorine resources, and the reaction conditions are harsh, making it difficult to achieve efficient, environmentally friendly and economical chlorine utilization.
The triboelectric material TiO2 is used as a catalyst to react with polyvinyl chloride and olefins or alcohol in a vibrating ball mill system, degrade PVC by mechanochemical method and synthesize chlorine organic matter to achieve efficient utilization of chlorine elements.
Under mild conditions, PVC degradation and chlorine resource recycling are achieved, which reduces raw material costs and safety risks, avoids solvent pollution, and improves reaction efficiency and chlorine utilization.
Smart Images

Figure CN120535828A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of polymer materials, and in particular to a method for upgrading and recycling polyvinyl chloride by mechanochemical catalysis. Background Art
[0002] Plastics are indispensable in modern life due to their numerous advantages, including low cost, light weight, durability, corrosion resistance, and high thermal and electrical insulation properties. Polyvinyl chloride (PVC), one of the most common plastics in our lives, is widely used in manufacturing, construction, packaging, and medical applications due to its unique structure.
[0003] However, as a hazardous plastic containing chlorine atoms, polyvinyl chloride (PVC) presents significant challenges in its waste disposal. Currently, PVC is typically disposed of by landfill or incineration. Direct landfilling of PVC waste generates significant waste, including additives such as potentially carcinogenic phthalates, which gradually seep into the surrounding environment. Incineration, due to its chemical composition, releases corrosive hydrochloric acid gas, as well as numerous environmentally hazardous substances such as dioxins and polychlorinated biphenyls. Both treatment methods can cause significant environmental damage.
[0004] At present, the dechlorination of polyvinyl chloride is still the focus of related research. Among the proposed methods for dechlorination of polyvinyl chloride, the mechanochemical method has attracted much attention. In 2004, Inoue et al. placed PVC and dry inorganic alkaline additives KOH and NaOH in the air, and used a planetary ball mill to grind them to explore the dechlorination reaction. The results showed that grinding can reduce the size of PVC and generate dechlorinated PVC and chlorides. The dechlorinated PVC contains C=C bonds, and the dechlorination rate increases with the grinding time and the amount of additives. The color of PVC deepens after dechlorination. In 2008, Xiao Songwen et al. used zinc powder as a catalyst to mechanochemically dechlorinate polyvinyl chloride (PVC) and polyvinylidene chloride (PVDC). Infrared spectroscopy and solid-state nuclear magnetic resonance characterized the structure of the dechlorinated polymer. In 2019, et al., due to the rich CaCO3 content in eggshells, co-grinded industrial PVC waste with eggshell waste. When the Ca:Cl (mol:mol) ratio was 5.06, complete dechlorination was achieved in 4 hours. In 2023, Kim et al. used a vibrating ball mill to demonstrate that the organic base 1,8-diazabicycloundec-7-ene (DBU) was more effective than inorganic bases in dechlorination. Using DBU as a dechlorination agent, complete dechlorination was achieved in 3 hours. The dechlorinated polymer product, polyacetylene, has unique physical and chemical properties that make it insoluble in any organic solvent.
[0005] Currently, alkali is commonly used as an additive in dechlorination operations using mechanical ball milling. However, the use of large amounts of alkali inevitably leads to additional environmental pollution problems, requiring subsequent neutralization with acid. Moreover, during this process, chlorine atoms are generally released as inorganic salts, making it difficult to further functionalize chlorine resources and resulting in the waste of chlorine atoms. Therefore, there is an urgent need to develop a more efficient, environmentally friendly, and economical method for dechlorinating polyvinyl chloride. Summary of the Invention
[0006] To solve the above technical problems, the present invention provides a method for upgrading and recycling polyvinyl chloride by mechanochemical catalysis. Triboelectric materials are introduced to catalyze the degradation of PVC in a vibrating ball mill system. At the same time, the chlorine element generated by PVC dechlorination can be used to efficiently synthesize chlorinated organic matter.
[0007] The present invention is achieved through the following technical solutions:
[0008] A method for mechanochemically catalyzing the upgrading and recycling of polyvinyl chloride comprises the following steps:
[0009] Putting polyvinyl chloride (PVC) and a triboelectric material into a ball mill jar, wherein the amount of the triboelectric material accounts for 10-60 wt% of the total amount of the polyvinyl chloride and the triboelectric material, then adding an olefin or an alcohol into the ball mill jar, placing the ball mill jar on a ball mill for a ball milling mechanochemical reaction, and obtaining products including chlorinated organic compounds after the reaction is completed;
[0010] The triboelectric material is TiO2;
[0011] The olefin is selected from one or more of styrene, 4-bromostyrene, 3-methoxystyrene, 4-trifluoromethylstyrene, 4-tert-butylstyrene, allylbenzene, 1-octene, cyclopentene, cyclohexene and cycloheptene.
[0012] To avoid waste of chlorine, the present invention combines the dechlorination of PVC with the hydrochlorination of olefins and the chlorination of alcohols to effectively utilize the chlorine in the PVC. The specific method involves using ball milling and triboelectric materials to mechanochemically degrade the PVC and recover the chlorine for use in synthesizing chlorinated organic compounds. Using PVC as a chlorine source and olefins or alcohols as substrates, the present invention, by adjusting the ratio of PVC, triboelectric material, and substrate, can produce chlorinated organic compounds with a high yield under solvent-free, mild conditions (normal temperature and pressure), achieving PVC degradation and chlorine resource recovery.
[0013] Furthermore, the crystal form of the TiO2 is anatase and / or rutile, preferably anatase.
[0014] Triboelectric materials play a crucial role in the entire process: catalyzing the dechlorination of PVC and activating the hydrochlorination of olefins or the chlorination of alcohols. There are many types of triboelectric materials, among which TiO2 (anatase) is most effective. Contact electrocatalysis is a type of mechanical catalysis. The contact electrocatalytic mechanism of the entire process can be considered as follows: in a ball mill system, the grinding balls and the triboelectric material rub against each other, and electrons accumulate on the surface of the triboelectric material. The electrons obtained by the PVC generate carbon free radicals and chloride anions, which then undergo an elimination reaction to generate hydrogen chloride gas. Simultaneously, the triboelectric material activates the olefin or alcohol to promote the chlorination reaction.
[0015] Furthermore, the amount of the triboelectric material is 10-50 wt % of the total amount of polyvinyl chloride and the triboelectric material, preferably 20-50 wt %, more preferably 40-50 wt %.
[0016] Furthermore, the molar ratio of the polyvinyl chloride to the olefin is (25-35):1.
[0017] Furthermore, the molar ratio of the polyvinyl chloride to the alcohol is (25-35):(1-5).
[0018] Furthermore, the ball mill is a zirconia ball mill.
[0019] Furthermore, the volume of the ball mill is 10-25 mL.
[0020] Furthermore, the ball mill jar contains 1-3 zirconium oxide grinding balls.
[0021] Furthermore, the diameter of the zirconia grinding balls is 10-20 mm.
[0022] Furthermore, the ball mill operates at a frequency of 10-30 Hz.
[0023] Furthermore, the ball milling mechanochemical reaction time is 1-4 hours.
[0024] Furthermore, the temperature of the ball milling mechanochemical reaction is 25-40°C.
[0025] Furthermore, the alcohol is selected from one or more of 1-phenylethanol, 4-(hydroxymethyl)benzaldehyde, 3-methyl-3-pentanol, tert-butanol, 2-hexanol, 1-heptanol, cyclopentanol, cyclohexanol, cycloheptanol and 1-adamantanol.
[0026] Furthermore, the structure of the PVC is Its number average molecular weight is 80-90 kDa.
[0027] Furthermore, the 1-chloro-1-phenylethane is a Markovnikov addition product, and the structural formula is
[0028] Furthermore, the product obtained after the reaction is completed also includes DPVC, which is a substance obtained by degrading PVC and has the structural formula:
[0029] In a specific embodiment, the reaction equation with PVC as the chlorine source, styrene as the substrate, and TiO2 as the triboelectric material is:
[0030]
[0031] In a specific embodiment, the reaction equation with PVC as the chlorine source, 1-phenylethanol as the substrate, and TiO2 as the triboelectric material is:
[0032]
[0033] The beneficial effects of the present invention are:
[0034] 1. The triboelectric material used in the present invention is cheap and easy to obtain, and is harmless to the environment. Compared with directly using HCl as a chlorine source, PVC as a chlorine source is safer and has lower cost.
[0035] 2. The present invention significantly reduces raw material costs and safety risks by using inexpensive triboelectric catalysts to replace traditional highly corrosive and expensive chlorination reagents; the reaction process does not require the use of organic solvents, effectively avoiding solvent pollution and recycling costs; at the same time, the reaction is carried out under mild conditions, without the need for harsh heat treatment such as high temperature and high pressure, significantly shortening the reaction time, improving reaction efficiency, and reducing energy consumption.
[0036] 3. The present invention connects the hydrogen chloride generated by PVC dechlorination with the hydrochlorination reaction of olefins and the chlorination reaction of alcohols in series, optimizes the good ratio of PVC, triboelectric material and substrate (olefins, alcohols), and achieves the dual goals of PVC degradation and chlorine resource recovery. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 This is the GC / MS spectrum of 1-chloro-1-phenylethane prepared in Example 1.
[0038] Figure 2 These are GPC spectra of PVC, DPVC prepared in Example 1 (with TiO2) and DPVC prepared in Comparative Example 1 (without TiO2).
[0039] Figure 3 This is the GC / MS spectrum of 1-chloro-1-phenylethane prepared in Example 6.
[0040] Figure 4 This is a physical picture of the commercial PVC gloves in Example 7.
[0041] Figure 5 This is a physical picture of the commercial PVC film in Example 8.
[0042] Figure 6 The 1-bromo-4-(1-chloroethyl)benzene prepared in Example 9 1 H NMR spectrum.
[0043] Figure 7 This is the GC / MS spectrum of 1-chloro-1-phenylethane prepared in Example 18.
[0044] Figure 8 This is the GC / MS spectrum of the product prepared in Comparative Example 1.
[0045] Figure 9 This is the GC / MS spectrum of the product prepared in Comparative Example 2.
[0046] Figure 10 This is the GC / MS spectrum of 1-chloro-1-phenylethane prepared in Comparative Example 3.
[0047] Figure 11 This is a photo of the Retsch Mixer mill MM 400 vibrating ball mill.
[0048] Figure 12 The figures are actual pictures of the zirconia grinding balls and zirconia ball mill jars in Examples 1-27 and Comparative Examples 1-5. DETAILED DESCRIPTION
[0049] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which this invention pertains. The terms used herein in the specification of the present invention are for the purpose of describing specific embodiments only and are not intended to limit the present invention. The term "and / or" as used herein includes any and all combinations of one or more of the associated listed items.
[0050] The present invention will be further described below with reference to the accompanying drawings and specific embodiments so that those skilled in the art can better understand the present invention and implement it. However, the embodiments are not intended to limit the present invention.
[0051] Unless otherwise specified, the experimental methods used in the following examples are conventional methods. The materials and reagents used are all commercially available unless otherwise specified. The vibrating ball mill used in the following examples and comparative examples is a Retsch Mixer mill MM 400 operating at a frequency of 30 Hz.
[0052] The yields of the reactions in the following examples and comparative examples were measured by gas chromatography-mass spectrometry (GC / MS) and nuclear magnetic resonance spectroscopy. The measuring instruments and test conditions were as follows: gas chromatography-mass spectrometry (Agilent), methanol as solvent, chlorobenzene as internal standard. Nuclear magnetic resonance spectroscopy (Bruker 300MHz) was used to measure the hydrogen nuclear magnetic resonance spectrum ( 1 H NMR) using d-DMSO as solvent. The number average molecular weight of polyvinyl chloride was determined by gel permeation chromatography (GPC).
[0053] Example 1
[0054] A method for mechanochemically catalyzing the upgrading and recycling of polyvinyl chloride comprises the following steps:
[0055] First, two zirconia grinding balls with a diameter of 10mm were placed in a 10mL zirconia ball mill, and then PVC (3.2mmol, 200mg), TiO2 (anatase type, the amount of TiO2 accounted for 50wt% of the total amount of PVC and TiO2, 200mg), and styrene (0.1mmol, 12μL) were added to the ball mill in sequence. The ball mill was then tightened and the tightly sealed ball mill was placed on a ball mill to react for 1h. After the reaction was completed, 3mL of anhydrous methanol was added as a solvent and 30μL of chlorobenzene as an internal standard. The mixture was then added to a 50mL centrifuge tube and centrifuged at 9600rpm for 6min. The supernatant was taken and filtered with a 0.45um filter head. It was characterized by GC / MS. The yield of 1-chloro-1-phenylethane was 88%. The GC / MS spectrum obtained by the test was as shown below. Figure 1 shown.
[0056] The remaining precipitate was dissolved in 15 mL of tetrahydrofuran (THF). After dissolving the degraded PVC (DPVC), the mixture was centrifuged at 9600 rpm for 10 min. The supernatant was then dried and the DPVC was collected. 10 mg of DPVC and 1.5 mL of THF were prepared to prepare a solution. The GPC spectrum obtained by testing was as follows: Figure 2 shown.
[0057] Example 2
[0058] A method for upgrading and recycling polyvinyl chloride by mechanochemical catalysis is basically the same as Example 1, except that the amount of TiO2 used is 23 mg, accounting for 10 wt% of the total amount of PVC and TiO2 used.
[0059] The yield of 1-chloro-1-phenylethane was determined to be 6.8% by GC / MS.
[0060] Example 3
[0061] A method for upgrading and recycling polyvinyl chloride by mechanochemical catalysis is basically the same as Example 1, except that the amount of TiO2 used is 50 mg, accounting for 20 wt% of the total amount of PVC and TiO2 used.
[0062] The yield of 1-chloro-1-phenylethane was determined to be 31% by GC / MS.
[0063] Example 4
[0064] A method for upgrading and recycling polyvinyl chloride by mechanochemical catalysis is basically the same as Example 1, except that the amount of TiO2 used is 86 mg, accounting for 30 wt% of the total amount of PVC and TiO2 used.
[0065] The yield of 1-chloro-1-phenylethane was determined to be 43% by GC / MS.
[0066] Example 5
[0067] A method for upgrading and recycling polyvinyl chloride by mechanochemical catalysis is basically the same as Example 1, except that the amount of TiO2 used is 134 mg, accounting for 40 wt% of the total amount of PVC and TiO2 used.
[0068] The yield of 1-chloro-1-phenylethane was determined to be 51% by GC / MS.
[0069] Example 6
[0070] A method for mechanochemically catalyzing the upgrading and recycling of polyvinyl chloride comprises the following steps:
[0071] First, two zirconia grinding balls with a diameter of 10mm were placed in a 10mL zirconia ball mill, and then PVC (3.2mmol, 200mg), TiO2 (rutile type, the amount of TiO2 accounted for 50wt% of the total amount of PVC and TiO2, 200mg), and styrene (0.1mmol, 12μL) were added to the ball mill in sequence. The ball mill was then tightened and the tightly sealed ball mill was placed on a ball mill to react for 1h. After the reaction was completed, 3mL of anhydrous methanol was added as a solvent and 30μL of chlorobenzene as an internal standard. The mixture was then added to a 50mL centrifuge tube and centrifuged at 9600rpm for 6min. The supernatant was taken and filtered with a 0.45um filter head. It was characterized by GC / MS. The yield of 1-chloro-1-phenylethane was 69%. The GC / MS spectrum obtained by the test was as shown below. Figure 3 shown.
[0072] Example 7
[0073] A method for upgrading and recycling polyvinyl chloride by mechanochemical catalysis is basically the same as Example 1, except that the source of PVC is treated commercial PVC gloves (see the actual picture). Figure 4 The treatment method is as follows: commercial PVC gloves are placed in a beaker, dissolved with tetrahydrofuran, centrifuged, and the supernatant is precipitated with methanol, and then filtered to obtain PVC; and a tightly sealed ball mill is placed on a ball mill for a reaction time of 4 hours.
[0074] The yield of 1-chloro-1-phenylethane was determined to be 91% by GC / MS.
[0075] Example 8
[0076] A method for recycling polyvinyl chloride by mechanochemical catalysis is basically the same as that in Example 1, except that the source of PVC is treated commercial PVC film (see the actual picture). Figure 5 The treatment method is as follows: a commercial PVC film is placed in a beaker, soaked in ethanol for 1 hour, and then filtered to obtain PVC; and a tightly sealed ball mill is placed on a ball mill for a reaction time of 4 hours.
[0077] The yield of 1-chloro-1-phenylethane was determined to be 87% by GC / MS.
[0078] Example 9
[0079] A method for mechanochemically catalyzing the upgrading and recycling of polyvinyl chloride comprises the following steps:
[0080] First, two zirconia grinding balls with a diameter of 10mm are placed in a 10mL zirconia ball mill. Then, PVC (3.2mmol, 200mg), TiO2 (the amount of TiO2 accounts for 50wt% of the total amount of PVC and TiO2, 200mg), and 4-bromostyrene (0.1mmol, 13μL) are added to the ball mill in sequence. Then, the ball mill is tightened and the tightly sealed ball mill is placed on a ball mill to react for 1h. After the reaction is completed, the ball mill is opened and 1.5mL of deuterated dimethyl sulfoxide (DMSO) containing 11mg of terephthalaldehyde is added. The mixture is then added to a 2mL centrifuge tube and centrifuged at 13500rpm for 2min. The supernatant is taken to prepare the solution and the reaction is carried out using a centrifuge. 1 H NMR characterization showed that the yield of 1-bromo-4-(1-chloroethyl)benzene was 86%. 1 H NMR spectrum Figure 6 shown.
[0081] Example 10
[0082] A method for mechanochemically catalyzing the upgrading and recycling of polyvinyl chloride comprises the following steps:
[0083] Two 10mm diameter zirconia grinding balls were placed in a 10mL zirconia mill. PVC (3.2mmol, 200mg), TiO2 (50wt%, 200mg), and 3-methoxystyrene (0.1mmol, 14μL) were then added to the mill. The mill was then tightened and placed on a ball mill to react for 1 hour. After the reaction, 1.5mL of deuterated DMSO containing 11mg of terephthalaldehyde was added to the mill. The mixture was then added to a 2mL centrifuge tube and centrifuged at 13500rpm for 2 minutes. The supernatant was collected for nuclear magnetic resonance (NMR) analysis, revealing a yield of 38% for 1-(1-chloroethyl)-3-methoxybenzene.
[0084] Example 11
[0085] A method for mechanochemically catalyzing the upgrading and recycling of polyvinyl chloride comprises the following steps:
[0086] Two 10mm diameter zirconia grinding balls were placed in a 10mL zirconia mill. PVC (3.2mmol, 200mg), TiO2 (50wt%, 200mg), and 4-trifluoromethylstyrene (0.1mmol, 15μL) were then added to the mill. The mill was then tightened and placed on a ball mill for 4 hours. After the reaction, 1.5mL of deuterated DMSO containing 11mg of terephthalaldehyde was added to the mill. The mixture was then added to a 2mL centrifuge tube and centrifuged at 13500rpm for 2 minutes. The supernatant was collected for nuclear magnetic resonance (NMR) analysis, revealing a yield of 21% for 1-(1-chloroethyl)-4-(trifluoromethyl)benzene.
[0087] Example 12
[0088] A method for mechanochemically catalyzing the upgrading and recycling of polyvinyl chloride comprises the following steps:
[0089] Two 10mm diameter zirconia grinding balls were placed in a 10mL zirconia mill. PVC (3.2mmol, 200mg), TiO2 (50wt%, 200mg), and 4-tert-butylstyrene (0.1mmol, 19μL) were then added to the mill. The mill was then tightened and placed on a ball mill to react for 1 hour. After the reaction, 1.5mL of deuterated DMSO containing 11mg of terephthalaldehyde was added to the mill. The mixture was then added to a 2mL centrifuge tube and centrifuged at 13500rpm for 2 minutes. The supernatant was collected for nuclear magnetic resonance (NMR) analysis, revealing a 40% yield of 1-tert-butyl-4-(1-chloroethyl)benzene.
[0090] Example 13
[0091] A method for mechanochemically catalyzing the upgrading and recycling of polyvinyl chloride comprises the following steps:
[0092] Two 10mm diameter zirconia grinding balls were placed in a 10mL zirconia mill. PVC (3.2mmol, 200mg), TiO2 (50wt%, 200mg), and allylbenzene (0.1mmol, 14μL) were then added to the mill. The mill was then tightened and placed on a ball mill for 4 hours. After the reaction, 1.5mL of deuterated DMSO containing 11mg of terephthalaldehyde was added to the mill. The mixture was then added to a 2mL centrifuge tube and centrifuged at 13500rpm for 2 minutes. The supernatant was collected for nuclear magnetic resonance (NMR) analysis, revealing a 41% yield of 2-chloropropylbenzene.
[0093] Example 14
[0094] A method for mechanochemically catalyzing the upgrading and recycling of polyvinyl chloride comprises the following steps:
[0095] Two 10mm diameter zirconia grinding balls were placed in a 10mL zirconia mill. PVC (3.2mmol, 200mg), TiO2 (50wt%, 200mg), and 1-octene (0.1mmol, 16μL) were then added to the mill. The mill was then tightened and placed on a ball mill for 4 hours. After the reaction, 1.5mL of deuterated DMSO containing 11mg of terephthalaldehyde was added to the mill. The mixture was then added to a 2mL centrifuge tube and centrifuged at 13500rpm for 2 minutes. The supernatant was collected for nuclear magnetic resonance (NMR) analysis, revealing a 50% yield of 2-chlorooctane.
[0096] Example 15
[0097] A method for mechanochemically catalyzing the upgrading and recycling of polyvinyl chloride comprises the following steps:
[0098] Two 10mm diameter zirconia grinding balls were placed in a 10mL zirconia ball mill. PVC (3.2mmol, 200mg), TiO2 (50wt%, 200mg), and cyclopentene (0.1mmol, 9μL) were then added to the mill. The mill was then tightened and placed on a ball mill for 4 hours. After the reaction, the mill was opened and 3mL of anhydrous methanol was added as the solvent, along with 30μL of chlorobenzene as the internal standard. The mixture was then added to a 50mL centrifuge tube and centrifuged at 9600rpm for 6 minutes. The supernatant was filtered through a 0.45μm filter and characterized by GC / MS. The yield of chlorinated cyclopentane was 10%.
[0099] Example 16
[0100] A method for mechanochemically catalyzing the upgrading and recycling of polyvinyl chloride comprises the following steps:
[0101] Two 10mm diameter zirconia grinding balls were placed in a 10mL zirconia ball mill. PVC (3.2mmol, 200mg), TiO2 (50wt%, 200mg), and cyclohexene (0.1mmol, 11μL) were then added to the mill. The mill was then tightened and placed on a ball mill for 4 hours. After the reaction, the mill was opened and 3mL of anhydrous methanol was added as the solvent, along with 30μL of chlorobenzene as the internal standard. The mixture was then added to a 50mL centrifuge tube and centrifuged at 9600rpm for 6 minutes. The supernatant was filtered through a 0.45μm filter and characterized by GC / MS. The yield of chlorinated cyclohexane was 31%.
[0102] Example 17
[0103] A method for mechanochemically catalyzing the upgrading and recycling of polyvinyl chloride comprises the following steps:
[0104] Two 10mm diameter zirconia grinding balls were placed in a 10mL zirconia ball mill. PVC (3.2mmol, 200mg), TiO2 (50wt%, 200mg), and cycloheptene (0.1mmol, 12μL) were then added to the mill. The mill was then tightened and placed on a ball mill to react for 4 hours. After the reaction, the mill was opened and 3mL of anhydrous methanol was added as the solvent, along with 30μL of chlorobenzene as the internal standard. The mixture was then added to a 50mL centrifuge tube and centrifuged at 9600rpm for 6 minutes. The supernatant was filtered through a 0.45μm filter and characterized by GC / MS. The yield of chlorinated cycloheptane was 50%.
[0105] Example 18
[0106] A method for mechanochemically catalyzing the upgrading and recycling of polyvinyl chloride comprises the following steps:
[0107] First, two zirconia grinding balls with a diameter of 10 mm were placed in a 10 mL zirconia ball mill. PVC (3.2 mmol, 200 mg), TiO2 (50 wt%, 200 mg), and 1-phenylethanol (0.3 mmol, 39 μL) were then added to the ball mill in sequence. The ball mill was then tightened and the tightly sealed ball mill was placed on a ball mill for 4 hours. After the reaction was completed, 3 mL of anhydrous methanol was added as a solvent and 30 μL of chlorobenzene as an internal standard. The mixture was then added to a 50 mL centrifuge tube and centrifuged at 9600 rpm for 6 minutes. The supernatant was taken and filtered with a 0.45 μm filter head. The supernatant was characterized by GC / MS. The yield of 1-chloro-1-phenylethane was 75%. The GC / MS spectrum obtained by the test was shown in FIG. Figure 7 shown.
[0108] Example 19
[0109] A method for mechanochemically catalyzing the upgrading and recycling of polyvinyl chloride comprises the following steps:
[0110] Two 10mm diameter zirconium oxide grinding balls were placed in a 10mL zirconium oxide ball mill. PVC (3.2mmol, 200mg), TiO2 (50wt%, 200mg), and 4-(hydroxymethyl)benzaldehyde (0.3mmol, 42mg) were then added to the mill. The mill was then tightened and placed in a ball mill for 4 hours. After the reaction, the mill was opened and 3mL of anhydrous methanol was added as the solvent, along with 30μL of chlorobenzene as the internal standard. The mixture was then added to a 50mL centrifuge tube and centrifuged at 9600rpm for 6 minutes. The supernatant was filtered through a 0.45μm filter and characterized by GC / MS. The yield of 4-(chloromethyl)benzaldehyde was 76%.
[0111] Example 20
[0112] A method for mechanochemically catalyzing the upgrading and recycling of polyvinyl chloride comprises the following steps:
[0113] Two 10mm diameter zirconium oxide grinding balls were placed in a 10mL zirconium oxide ball mill. PVC (3.2mmol, 200mg), TiO2 (50wt%, 200mg), and 3-methyl-3-pentanol (0.3mmol, 13μL) were then added to the mill. The mill was then tightened and placed in a ball mill for 4 hours. After the reaction, the mill was opened and 3mL of anhydrous methanol was added as the solvent, along with 30μL of chlorobenzene as the internal standard. The mixture was then added to a 50mL centrifuge tube and centrifuged at 9600rpm for 6min. The supernatant was filtered using a 0.45μm filter and characterized by GC / MS. The yield of 3-chloro-3-methylpentane was 93%.
[0114] Example 21
[0115] A method for mechanochemically catalyzing the upgrading and recycling of polyvinyl chloride comprises the following steps:
[0116] Two 10mm diameter zirconia grinding balls were placed in a 10mL zirconia ball mill. PVC (3.2mmol, 200mg), TiO2 (50wt%, 200mg), and tert-butyl alcohol (0.3mmol, 24mg) were then added to the mill. The mill was then tightened and placed on a ball mill to react for 4 hours. After the reaction, the mill was opened and 3mL of anhydrous methanol was added as the solvent, along with 30μL of chlorobenzene as the internal standard. The mixture was then added to a 50mL centrifuge tube and centrifuged at 9600rpm for 6 minutes. The supernatant was filtered through a 0.45μm filter and characterized by GC / MS. The yield of tert-butyl chloride was 67%.
[0117] Example 22
[0118] A method for mechanochemically catalyzing the upgrading and recycling of polyvinyl chloride comprises the following steps:
[0119] Two 10mm diameter zirconia grinding balls were placed in a 10mL zirconia ball mill. PVC (3.2mmol, 200mg), TiO2 (50wt%, 200mg), and 2-hexanol (0.3mmol, 39μL) were then added to the mill. The mill was then tightened and placed on a ball mill for 4 hours. After the reaction, the mill was opened and 3mL of anhydrous methanol was added as the solvent, along with 30μL of chlorobenzene as the internal standard. The mixture was then added to a 50mL centrifuge tube and centrifuged at 9600rpm for 6 minutes. The supernatant was filtered through a 0.45μm filter and characterized by GC / MS. The yield of 2-chlorohexane was 31%.
[0120] Example 23
[0121] A method for mechanochemically catalyzing the upgrading and recycling of polyvinyl chloride comprises the following steps:
[0122] Two 10mm diameter zirconia grinding balls were placed in a 10mL zirconia mill. PVC (3.2mmol, 200mg), TiO2 (50wt%, 200mg), and 1-heptanol (0.3mmol, 42μL) were then added to the mill. The mill was then tightened and placed on a ball mill to react for 4 hours. After the reaction, the mill was opened and 3mL of anhydrous methanol was added as the solvent, along with 30μL of chlorobenzene as the internal standard. The mixture was then added to a 50mL centrifuge tube and centrifuged at 9600rpm for 6 minutes. The supernatant was filtered through a 0.45μm filter and characterized by GC / MS. The yield of 1-chloroheptane was 27%.
[0123] Example 24
[0124] A method for mechanochemically catalyzing the upgrading and recycling of polyvinyl chloride comprises the following steps:
[0125] Two 10mm diameter zirconium oxide grinding balls were placed in a 10mL zirconium oxide ball mill. PVC (3.2mmol, 200mg), TiO2 (50wt%, 200mg), and cyclopentanol (0.3mmol, 27μL) were then added to the mill. The mill was then tightened and placed on a ball mill for 4 hours. After the reaction, the mill was opened and 3mL of anhydrous methanol was added as the solvent, along with 30μL of chlorobenzene as the internal standard. The mixture was then added to a 50mL centrifuge tube and centrifuged at 9600rpm for 6 minutes. The supernatant was filtered through a 0.45μm filter and characterized by GC / MS. The yield of chlorinated cyclopentane was 68%.
[0126] Example 25
[0127] A method for mechanochemically catalyzing the upgrading and recycling of polyvinyl chloride comprises the following steps:
[0128] Two 10mm diameter zirconia grinding balls were placed in a 10mL zirconia ball mill. PVC (3.2mmol, 200mg), TiO2 (50wt%, 200mg), and cyclohexanol (0.3mmol, 30μL) were then added to the mill. The mill was then tightened and placed on a ball mill to react for 4 hours. After the reaction, the mill was opened and 3mL of anhydrous methanol was added as the solvent, along with 30μL of chlorobenzene as the internal standard. The mixture was then added to a 50mL centrifuge tube and centrifuged at 9600rpm for 6 minutes. The supernatant was filtered through a 0.45μm filter and characterized by GC / MS. The yield of chlorinated cyclohexane was 53%.
[0129] Example 26
[0130] A method for mechanochemically catalyzing the upgrading and recycling of polyvinyl chloride comprises the following steps:
[0131] Two 10mm diameter zirconium oxide grinding balls were placed in a 10mL zirconium oxide ball mill. PVC (3.2mmol, 200mg), TiO2 (50wt%, 200mg), and cycloheptanol (0.3mmol, 36μL) were then added to the mill. The mill was then tightened and placed on a ball mill to react for 4 hours. After the reaction, the mill was opened and 3mL of anhydrous methanol was added as the solvent, along with 30μL of chlorobenzene as the internal standard. The mixture was then added to a 50mL centrifuge tube and centrifuged at 9600rpm for 6 minutes. The supernatant was filtered with a 0.45μm filter and characterized by GC / MS. The yield of chlorinated cycloheptane was 47%.
[0132] Example 27
[0133] A method for mechanochemically catalyzing the upgrading and recycling of polyvinyl chloride comprises the following steps:
[0134] Two 10mm-diameter zirconia grinding balls were placed in a 10mL zirconia ball mill. PVC (3.2mmol, 200mg), TiO2 (50wt%, 200mg), and 1-adamantanol (0.3mmol, 45mg) were then added to the mill. The mill was then tightened and placed on a ball mill for 4 hours. After the reaction, the mill was opened and 3mL of anhydrous methanol and 30μL of chlorobenzene were added as an internal standard. The mixture was then added to a 50mL centrifuge tube and centrifuged at 9600rpm for 6 minutes. The supernatant was filtered through a 0.45μm filter and characterized by GC / MS. The yield of 1-chloroadamantane was 90%.
[0135] Comparative Example 1
[0136] A method for mechanochemically catalyzing the upgrading and recycling of polyvinyl chloride comprises the following steps:
[0137] First, two zirconia grinding balls with a diameter of 10 mm were placed in a 10 mL zirconia ball mill. PVC (3.2 mmol, 200 mg) and styrene (0.1 mmol, 12 μL) were then added to the ball mill in sequence. The ball mill was then tightened and the tightly sealed ball mill was placed on a ball mill for 1 hour. After the reaction was completed, 3 mL of anhydrous methanol was added as a solvent and 30 μL of chlorobenzene as an internal standard. The mixture was then added to a 50 mL centrifuge tube and centrifuged at 9600 rpm for 6 minutes. The supernatant was taken and filtered with a 0.45 μm filter head. The supernatant was characterized by GC / MS. The yield of 1-chloro-1-phenylethane was <1%. The GC / MS spectrum of the product obtained was shown in the figure below. Figure 8 shown.
[0138] The remaining precipitate was dissolved in 15 mL of tetrahydrofuran (THF). After dissolving the degraded PVC (DPVC), the mixture was centrifuged at 9600 rpm for 10 min. The supernatant was then dried and the DPVC was collected. 10 mg of DPVC and 1.5 mL of THF were prepared to prepare a solution. The GPC spectrum obtained by testing was as follows: Figure 2 shown.
[0139] Comparative Example 2
[0140] A method for mechanochemically catalyzing the upgrading and recycling of polyvinyl chloride comprises the following steps:
[0141] First, two zirconia grinding balls with a diameter of 10 mm were placed in a 10 mL zirconia ball mill. Then, PVC (3.2 mmol, 200 mg), BaTiO3 (the amount of BaTiO3 accounted for 50 wt% of the total amount of PVC and BaTiO3, 200 mg), and styrene (0.1 mmol, 12 μL) were added to the ball mill in sequence. The ball mill was then tightened and the tightly sealed ball mill was placed on a ball mill for reaction for 1 hour. After the reaction was completed, 3 mL of anhydrous methanol was opened and added as a solvent and 30 μL of chlorobenzene as an internal standard. The mixture was then added to a 50 mL centrifuge tube and centrifuged at 9600 rpm for 6 minutes. The supernatant was taken and filtered with a 0.45 μm filter head. The supernatant was characterized by GC / MS. The yield of 1-chloro-1-phenylethane was <1%. The GC / MS spectrum of the product obtained was shown in the figure. Figure 9 shown.
[0142] Comparative Example 3
[0143] A method for mechanochemically catalyzing the upgrading and recycling of polyvinyl chloride comprises the following steps:
[0144] First, two zirconia grinding balls with a diameter of 10 mm were placed in a 10 mL zirconia ball mill. Then, PVC (3.2 mmol, 200 mg), SiO2 (the amount of SiO2 accounted for 50 wt% of the total amount of PVC and SiO2, 200 mg), and styrene (0.1 mmol, 12 μL) were added to the ball mill in sequence. The ball mill was then tightened and the tightly sealed ball mill was placed on a ball mill to react for 1 hour. After the reaction was completed, 3 mL of anhydrous methanol was opened and added as a solvent and 30 μL of chlorobenzene as an internal standard. The mixture was then added to a 50 mL centrifuge tube and centrifuged at 9600 rpm for 6 minutes. The supernatant was taken and filtered with a 0.45 μm filter head. The supernatant was characterized by GC / MS. The yield of 1-chloro-1-phenylethane was 66%. The GC / MS spectrum obtained by the test was as shown below. Figure 10 shown.
[0145] Comparative Example 4
[0146] A method for mechanochemically catalyzing the upgrading and recycling of polyvinyl chloride comprises the following steps:
[0147] Two 10mm diameter zirconia grinding balls were placed in a 10mL zirconia mill. PVC (3.2mmol, 200mg), TiO2 (50wt%, 200mg), and 4-methoxystyrene (0.1mmol, 14μL) were then added to the mill. The mill was then tightened and placed on a ball mill to react for 1 hour. After the reaction, 1.5mL of deuterated DMSO containing 11mg of terephthalaldehyde was added to the mill. The mixture was then added to a 2mL centrifuge tube and centrifuged at 13500rpm for 2 minutes. The supernatant was collected for nuclear magnetic resonance (NMR) analysis, revealing a yield of <1% for 1-(1-chloroethyl)-4-methoxybenzene.
[0148] Comparative Example 5
[0149] A method for mechanochemically catalyzing the upgrading and recycling of polyvinyl chloride comprises the following steps:
[0150] Two 10mm diameter zirconia grinding balls were placed in a 10mL zirconia ball mill. PVC (3.2mmol, 200mg), TiO2 (50wt%, 200mg), and cis-cyclooctene (0.1mmol, 14μL) were then added to the mill. The mill was then tightened and placed on a ball mill to react for 4 hours. After the reaction, the mill was opened and 3mL of anhydrous methanol as the solvent and 30μL of chlorobenzene as the internal standard were added. The mixture was then added to a 50mL centrifuge tube and centrifuged at 9600rpm for 6 minutes. The supernatant was filtered through a 0.45μm filter and characterized by GC / MS. The yield of chlorinated cyclooctanes was less than 1%.
[0151] The ball mill in Examples 1-27 and Comparative Examples 1-5 is a Retsch Mixer mill MM 400 vibrating ball mill, as shown in the figure. Figure 11 The actual pictures of the zirconia grinding balls and zirconia ball mills in Examples 1-27 and Comparative Examples 1-5 are as shown in FIG. Figure 12 shown.
[0152] Obviously, the above embodiments of the present invention are merely examples for the purpose of clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. Those skilled in the art will appreciate that other variations or modifications may be made based on the above description. It is not necessary and impossible to enumerate all embodiments here. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention shall be included within the scope of protection of the claims of the present invention.
Claims
1. A method for upgrading and recycling polyvinyl chloride by mechanochemical catalysis, characterized in that: The following steps are involved: Putting polyvinyl chloride and a triboelectric material into a ball mill, wherein the amount of the triboelectric material accounts for 10-60 wt% of the total amount of the polyvinyl chloride and the triboelectric material, then adding an olefin or an alcohol into the ball mill, placing the ball mill on a ball mill for a ball milling mechanochemical reaction, and obtaining products including chlorinated organic compounds after the reaction is completed; The triboelectric material is TiO2; The olefin is selected from one or more of styrene, 4-bromostyrene, 3-methoxystyrene, 4-trifluoromethylstyrene, 4-tert-butylstyrene, allylbenzene, 1-octene, cyclopentene, cyclohexene and cycloheptene.
2. The method according to claim 1, characterized in that The crystal form of the TiO2 is anatase and / or rutile.
3. The method according to claim 1, characterized in that The amount of the triboelectric material used accounts for 10-50 wt% of the total amount of polyvinyl chloride and the triboelectric material.
4. The method according to claim 1, wherein The molar ratio of the polyvinyl chloride to the olefin is (25-35):
1.
5. The method according to claim 1, wherein The molar ratio of the polyvinyl chloride to the alcohol is (25-35):(1-5).
6. The method according to claim 1, characterized in that The ball mill operates at a frequency of 10-30 Hz.
7. The method according to claim 1, characterized in that The time of the ball milling mechanochemical reaction is 1-4 hours.
8. The method according to claim 1, characterized in that The temperature of the ball milling mechanochemical reaction is 25-40°C.
9. The method according to claim 1, characterized in that The alcohol is selected from one or more of 1-phenylethanol, 4-(hydroxymethyl)benzaldehyde, 3-methyl-3-pentanol, tert-butanol, 2-hexanol, 1-heptanol, cyclopentanol, cyclohexanol, cycloheptanol and 1-adamantanol.
10. The method according to claim 1, characterized in that The ball milling jar is a zirconia ball milling jar.